Entre beats e rimas: fusão de línguas e identidades nas músicas urbanas em Portugal - Marques, Isabelle Simões (2020)
The current urban music in Portugal is the meeting of different cultures and linguistic minorities. The linguistic repertoire of most of these artists includes different varieties of Portuguese, Creole (of Cape Verde and Sao Tome) and different African dialects (mostly Bantu languages of Angola). In this article, we analyse the bilingualism (code-switching and code-mixing) within the songs, produced by artists who reflect their multiculturalism in the lyrics of their songs. In fact, the performers alternate languages for the internal and external levels of the sentence. They also use a mixed style with a Portuguese matrix and lexicon of different languages, reflecting the urban vernacular languages and spreading their multiple identities.